A sub-150-nanometre-thick and ultraconformable solution-processed all-organic transistor - Fabrizio Antonio Viola (Nature Portfolio, 2021)
Reducing the thickness of flexible electronics is crucial to achieve better conformability and mechanical flexibility. Here, the authors demonstrate all-solution processed OFET with total thickness < 150 nm, with high transparency, which allows the device to conformally adhere onto non-planar surfaces, such as human skin.